2023
DOI: 10.7150/jca.77322
|View full text |Cite
|
Sign up to set email alerts
|

Platycodin D confers oxaliplatin Resistance in Colorectal Cancer by activating the LATS2/YAP1 axis of the hippo signaling pathway

Abstract: Oxaliplatin-based therapy is used as a first-line drug to treat metastatic colorectal cancer. However, long-term and repeated drug treatment resulted in drug resistance and the failure of chemotherapy. Various natural compounds were previously reported to act as chemosensitizers to reverse drug resistance. In this study, we found that platycodin D (PD), a saponin found in Platycodon grandiflorum, inhibited LoVo and OR-LoVo cells proliferation, invasion, and migration ability. Our results indicated that combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…Consistent with its central tumor-suppressor role, somatic alterations of the core Hippo pathway genes have been observed in various cancer types, including malignant pleural mesothelioma, cervical squamous cell carcinoma, meningioma, head and neck squamous cell carcinoma, uveal melanoma, and cholangiocarcinoma, among others [6][7][8]. In about 30-40% of malignant pleural mesothelioma cases, for example, the NF2 (Neurofibromatosis type 2) tumor suppressor gene is somatically inactivated, leading to defective recruitment 2 of 16 of LATS1/2 kinases to the plasma membrane and impaired Hippo signaling [9,10].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Consistent with its central tumor-suppressor role, somatic alterations of the core Hippo pathway genes have been observed in various cancer types, including malignant pleural mesothelioma, cervical squamous cell carcinoma, meningioma, head and neck squamous cell carcinoma, uveal melanoma, and cholangiocarcinoma, among others [6][7][8]. In about 30-40% of malignant pleural mesothelioma cases, for example, the NF2 (Neurofibromatosis type 2) tumor suppressor gene is somatically inactivated, leading to defective recruitment 2 of 16 of LATS1/2 kinases to the plasma membrane and impaired Hippo signaling [9,10].…”
Section: Introductionmentioning
confidence: 74%
“…Aberrant activation of TEAD-family transcription factors (TEADs) is a central determinant of oncogenic transformation in cancers characterized by dysregulation of the Hippo signaling pathway. Genetic inactivation of core genes within this tumor-suppressor kinase cascade (for example, about 35% to 40% of malignant pleural mesotheliomas cases carry an inactivating mutations at the neurofibromatosis 2, NF2, locus) or genetic amplification of YAP/TAZ transcriptional regulator (for example, more than 15% of cervical squamous cell carcinoma are driven by YAP/TAZ amplification) converge on TEAD transcription factors to establish an oncogenic transcriptional program that promotes uncontrolled cell proliferation [6,10]. This convergence highlights TEAD's centrality and establishes TEAD as a classic example of "non-oncogene addiction" that could be targeted therapeutically [41].…”
Section: Discussionmentioning
confidence: 99%
“…In CRC cell models, constitutive YAP activation reinforced the expression of the stemness biomarkers and regulators ALDH1A3, LGR5, and OCT4. The four main components of the Hippo pathway, MST1, LATS1/2, YAP, and TAZ, have also been shown to play a role in the development of chemoresistance, such as to 5-fluoruracil and oxalipatin [ 117 , 118 ].…”
Section: Targeted Drug Modulation Of Stemness Pathwaysmentioning
confidence: 99%
“…Regarding the mechanism of cancers being resistant to oxaliplatin, scientists have discovered several important biological pathways involved in the development of drug resistance. These include but are not limited to (1) the development of apoptosis inhibition and immunological tolerance, (2) nonspecific drug efflux and detoxification, and (3) specific DNA damage repair. To overcome the daunting challenge posed by oxaliplatin resistance, scientists are committed to finding chemosensitizers that can effectively restore oxaliplatin sensitivity. These approaches are mainly based on the resistance mechanisms relevant to the immune and apoptosis evasion of tumor cells. For instance, Liu’s group reported that the natural compound scutellarin could resensitize oxaliplatin activity against resistant CRC cells through ininhibition of the PKM2 enzyme, which is responsible for PDL-1 expression (Figure ).…”
Section: Introductionmentioning
confidence: 99%